Muslim Perception on Zakat as A Tax Deduction in Indonesia - Setiawan bin Lahuri; Husnul Khotimah; Ainun Amalia Zuhroh (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
This study aims to examine the Muslim community's perception of tax-deductible zakat in Indonesia. We employ exogenous variables including religiosity, halal and haram aspects, legal aspects, trust, motivation, and satisfaction. We also use variables of perception as mediating variables. The research data was collected through the distribution of questionnaires to 543 Muslims from various parts of Indonesia. This study employs Structural Equation Modeling with PLS version 3.0 to analyze the data. The results indicate that religiosity, the legal aspect, trust, and satisfaction have a positive and statistically significant effect on performance, whereas the halal-haram aspect and motivation have a negative and statistically significant effect on the tax deduction of zakat.========================================================================================================ABSTRAK – Persepsi Masyarakat Muslim Indonesia terhadap Zakat sebagai Pengurang Pajak. Penelitian ini bertujuan untuk menganalisis persepsi masyarakat muslim terhadap zakat pengurang pajak di Indonesia dengan mengunakan religiusitas, aspek halal haram, aspek legal, kepercayaan, motivasi dan kepuasan sebagai variabel eksogen, sedangkan persepsi digunakan sebagai variabel mediasi. Data penelitian diperoleh dari penyebaran kuesioner kepada 543 Muslim dari berbagai wilayah di Indonesia. Analisis dilakukan dengan Structural Equation Modeling dengan PLS versi 3.0. Hasil penelitian menunjukkan bahwa religiusitas, aspek legal, kepercayaan, dan kepuasan berpengaruh positif dan signifikan terhadap kinerja, sedangkan aspek halal haram and motivasi berpengaruh negatif dan signifikan terhadap sistem zakat pengurang pajak.